Natural material adsorbed onto a polymer to enhance immune function - Reinaque AP; França EL; Scherer EF; Côrtes MA; Souto FJ; Honorio-França AC (Dove Medical Press, 2012)
Ana Paula Barcelos Reinaque,1 Eduardo Luzía França,2 Edson Fredulin Scherer,3 Mayra Aparecida Côrtes,1 Francisco José Dutra Souto,4 Adenilda Cristina Honorio-França51Post Graduate Program in Material Science, 2Institute of Biological and Health Science, Federal University of Mato Grosso, Barra do Garças, 3Post Graduate Program in Material Science, Institute of Biological and Health Science, Federal University of Mato Grosso, Pontal do Araguaia, 4Faculty of Medical Sciences, Federal University of Mato Grosso, Cuiabá, 5Institute of Biological and Health Science, Federal University of Mato Grosso, Pontal do Araguaia, MT, BrazilBackground: In this study, we produced poly(ethylene glycol) (PEG) microspheres of different sizes and adsorbing a medicinal plant mixture, and verified their effect in vitro on the viability, superoxide production, and bactericidal activity of phagocytes in the blood.Methods: The medicinal plant mixture was adsorbed onto PEG microspheres and its effects were evaluated by flow cytometry and fluorescence microscopy.Results: Adsorption of the herbal mixture onto the PEG microspheres was achieved and the particles were internalized by phagocytes. PEG microspheres bearing the adsorbed herbal mixture stimulated superoxide release, and activated scavenging and microbicidal activity in phagocytes. No differences in functional activity were observed when the phagocytes were not incubated with PEG microspheres bearing the adsorbed herbal mixture.Conclusion: This system may be useful for the delivery of a variety of medicinal plants and can confer additional protection against infection. The data reported here suggest that a polymer adsorbed with a natural product is a treatment alternative for enhancing immune function.Keywords: natural product, polymer, adsorption, immune function, phagocytes